Intersectional pedagogy : Complicating identity and social justice - Case, Kim A. (Routledge, 2017)
Intersectional Pedagogy explores best practices for effective teaching and learning about intersections of identity as informed by intersectional theory. Formatted in three easy-to-follow sections, this collection explores the pedagogy of intersectionality to address lived experiences that result from privileged and oppressed identities. After an initial overview of intersectional foundations and theory, the collection offers classroom strategies and approaches for teaching and learning about intersectionality and social justice. With contributions from scholars in education, psychology, sociology and women’s studies, Intersectional Pedagogy include a range of disciplinary perspectives and evidence-based pedagogy.
Keywords: approches et analyses; discipline; formations; féminisme décolonial; identités; intersectionnalité; justice sociale; outils; ouvrages de références; psychologie; pédagogie; ressource en ligne; sciences de l'éducation; sciences humaines; sociologie; thématiques; études de genres

The pedagogical practices of Québec high school teachers relative to sexual diversity - Richard, Gabrielle (Journal of LGBT Youth, 2015)
This article explores the ways in which teachers describe their pedagogical and intervention practices relative to sexual diversity in Québec (Canada). Three variables closely associated with teachers who report inclusive practices emerge: experiential training (based on the experience of a lesbian, gay, or bisexual [LGB] teacher), contact training (from close acquaintance with LGB individuals), and professional training. These factors impact the probability that a teacher will refer to homosexuality, intervene when homophobic incidents occur to deconstruct prejudices, and become the confidant of LGBQ students. Results are discussed based on research on minority teachers and on the roles of straight allies in education.
Number: 2 https://www.researchgate.net/publication/276111985_The_Pedagogical_Practices_of_Quebec_High_School_Teachers_Relative_to_Sexual_Diversity
Keywords: EDI; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; discipline; diversité sexuelle; formations; homophobie; hétérosexisme; identités LGBTQIA2+; outils; québec; ressource en ligne; régions géographiques; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques; travail; école secondaire

Project Implicit
Test de préjugés inconscients
Keywords: approches et analyses; biais inconscients; cours; discipline; discours dominant; formations; inégalités; outils; pol5480; premier cycle; privilèges; psychologie; pédagogie; racisme; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences